2008
DOI: 10.5424/sjar/2008061-291
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ageing method, ageing period, cooking method and sample thickness on beef textural characteristics

Abstract: The effect of the ageing method (bone-in or boneless), ageing period (7 or 14 days), cooking method (grilling or water bath preparation) and sample thickness (1, 2 or 4 cm) on the meat texture characteristics of the longissimus thoracis muscle of six young, commercial bulls was measured using a texture analyser incorporating compression and Warner-Bratzler devices. The sarcomere length of the raw meat and cooking losses were also recorded. The ageing method and ageing period had more influence on the textural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
0
15
0
3
Order By: Relevance
“…The degree of protein denaturation, which implies the change in their structure, is mainly related to the rate of heat flux penetration to the surface of meat portion, as well as the heat conduction inside the product during thermal treatment (Panea et al, 2008). During the heating of meat, the denaturation of major proteins, such as myosin, sarcoplasmic protein, collagen and actin occurs at different temperatures (Ishiwatari et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of protein denaturation, which implies the change in their structure, is mainly related to the rate of heat flux penetration to the surface of meat portion, as well as the heat conduction inside the product during thermal treatment (Panea et al, 2008). During the heating of meat, the denaturation of major proteins, such as myosin, sarcoplasmic protein, collagen and actin occurs at different temperatures (Ishiwatari et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Temperature difference between heating medium and meat surface has a significant effect on the rate and extent of protein structure changes. In the meantime, thermal processing can usually influence the sensory properties of the final product (Drummond & Sun, 2006;Panea et al, 2008). Thermal processing of food is defined as the delivery of heat to the products.…”
Section: Introductionmentioning
confidence: 99%
“…This difference could be due to different cooking methods resulting overall in more important cooking losses in the present study (around 30%) compared with the previous one (around 20%), albeit in the range reported by other studies (Safari et al 2002;Hopkins et al 2006). Cooking methods have been shown to influence cooking loss in beef (Panea et al 2008).…”
Section: Cooking Loss and Tendernessmentioning
confidence: 99%
“…Cooking method has the most important effect on cooking loss with several influencing variables consist of meat surface, heat transfer method, and internal temperature (Panea et al, 2008). Soeparno (2005) reported that body area from which the muscle is sampled also influences cooking loss.…”
Section: Cooking Lossmentioning
confidence: 99%